The European Organisation for Research and Treatment of Cancer, State of Science in radiation oncology and priorities for clinical trials meeting report. (May 2020) - Thomas, Gillian; Eisenhauer, Elizabeth; Bristow, Robert G.; Grau, Cai; Hurkmans, Coen; Ost, Piet; Guckenberger, Matthias; Deutsch, Eric; Lacombe, Denis; Weber, Damien C.; ,
Abstract: Background: New technologies and techniques in radiation oncology and imaging offer opportunities to enhance the benefit of loco-regional treatments, expand treatment to new patient populations such as those with oligometastatic disease and decrease normal tissue toxicity. Furthermore, novel agents have become available which may be combined with radiation therapy, and identification of radiation-related biomarkers can be studied to refine treatment prescriptions. Finally, the use of artificial intelligence (AI) capabilities may also improve treatment quality assurance or the ease with which radiation dosing is prescribed. All of these potential advances present both opportunities and challenges for academic clinical researchers. Methods: Recently, the European Organisation for Research and Treatment of Cancer addressed these topics in a meeting of multiple stakeholders from Europe and North America. The following five themes radiobiology-based biomarkers, new technologies – particularly proton beam therapy, combination systemic and radiation therapy, management of oligometastatic disease and AI opportunities in radiation oncology were discussed in a State of Science format to define key controversies, unanswered questions and propose clinical trial priorities for development. Conclusions: Priorities for clinical trials implementing new science and technologies have been defined. Solutions to integrate the multidimensional complexity of data have been explored. New types of platforms and partnerships can support innovative approaches for clinical research in radiation oncology. Highlights: Biomarkers of radiation sensitivity are ready for randomised prospective evaluation. RCTS (Randomised Clinical Trials) of proton therapy should examine impacts on toxicity and efficacy. Artificial intelligence may improve the quality of radiation treatment delivery. Cure is the key end-point for trials of ablative radiation in oligometastases. New systemic therapy plus radiation should be evaluated to improve disease control.